Two-photon imaging of formaldehyde in live cells and animals utilizing a lysosome-targetable and acidic pH-activatable fluorescent probe. Issue 48 (2nd June 2017) - Xie, Xilei; Tang, Fuyan; Shangguan, Xiaoyan; Che, Shiyi; Niu, Jinye; Xiao, Yongsheng; Wang, Xu; Tang, Bo
Abstract : A two-photon fluorescent probe presented lysosomal targetability and an acidic pH-activatable response toward formaldehyde, and was applied to visualize formaldehyde in living systems. Abstract : Lyso-TPFP presents lysosomal targetability and an acidic pH-activatable response toward formaldehyde. Thus, it exclusively visualizes lysosomal formaldehyde and is immune against it in neutral cytosol and other organelles. In addition, two-photon fluorescence imaging endows Lyso-TPFP with the capability of in situ tracking formaldehyde in live cells and animals.